1989
DOI: 10.1172/jci114145
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-induced anorexia in the rat. Influence of prostaglandins.

Abstract: The anorexia associated with acute and chronic inflammatory or infectious conditions is poorly understood. Our objectives were to explore the anorexigenic effects of interleukin-1 (IL-1) in the rat. Recombinant human (rh) IL-1,6, murine (rm) IL-la and to a lesser extent rhIL-la significantly reduced food intake at 24.0 gg/kg i.p. but not at lower doses, in young (200-250 g) meal-fed rats on chow diets. The anorexic effect appears to be mediated by prostaglandins since pretreatment with ibuprofen completely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
2
4

Year Published

1993
1993
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(123 citation statements)
references
References 51 publications
10
107
2
4
Order By: Relevance
“…Similar material has also been detected in the plasma of cancer patients with weight loss greater than 10% (Belizario et al, 1991). The nature of this material is not known, although some studies have suggested that the cytokines tumour necrosis factor alpha (TNF-a) (Flores et al, 1989), alone or in combination with interleukin-1 (Hellerstein et al, 1989) Muscle from non tumour-bearing animal potential candidate for this role is the polyunsaturated fatty acid arachidonic acid. Arachidonate has been shown to both inhibit protein synthesis (Rotman et al, 1992) and increase protein degradation in skeletal muscle (Rodeman & Goldberg, 1982), the latter by the mediation of a prostaglandin E2 (PGE2) intermediate.…”
Section: Discussionmentioning
confidence: 86%
“…Similar material has also been detected in the plasma of cancer patients with weight loss greater than 10% (Belizario et al, 1991). The nature of this material is not known, although some studies have suggested that the cytokines tumour necrosis factor alpha (TNF-a) (Flores et al, 1989), alone or in combination with interleukin-1 (Hellerstein et al, 1989) Muscle from non tumour-bearing animal potential candidate for this role is the polyunsaturated fatty acid arachidonic acid. Arachidonate has been shown to both inhibit protein synthesis (Rotman et al, 1992) and increase protein degradation in skeletal muscle (Rodeman & Goldberg, 1982), the latter by the mediation of a prostaglandin E2 (PGE2) intermediate.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies suggest that the cytokine tumour necrosis factor alpha (TNF-a) (Flores et al, 1989) alone, or in combination with interleukin-I (IL-l) (Hellerstein et al, 1989) increase muscle proteolysis through a prostaglandin intermediate. A proteolysis-inducing factor has been shown to be present in the plasma proteins of 25 out of 50 cancer patients with weight loss and in five of these samples the bioactivity was partially abrogated with antibodies to recombinant IL-1 (Belizario et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, eicosanoids appear to be involved in these responses, because the reductions in ingestive behavior induced by IL-1 are largely prevented by COX inhibitors, such as indomethacin [183,186]. However, such inhibitors are less effective against the LPS-induced behavioral changes [183,187], and have only small effects on the behavioral changes associated with influenza virus infection [183].…”
Section: The Neurochemical Involvement In Behavioral Responses To Cytmentioning
confidence: 99%